Biaya Kompensasi Dan Biaya Program Kesejahteraan Dengan Kinerja - Ibni Humam; Habibi Zayan (Jurnal Teknik dan Teknologi Indonesia, 2023)
Based on Law Number 48 of 2008 concerning Education Funding, Part Five, Article 27 paragraph (1), states that the government and local governments according to their authority provide tuition assistance or scholarships to students whose parents or guardians cannot afford to pay for their education. Article 27 paragraph (2), states that the government and regional governments according to their authority can provide scholarships to outstanding students